The use of historical range and variability (HRV) in landscape management - Keane, Robert E.; Hessburg, Paul F.; Landres, Peter B.; Swanson, Fred J. (Forest ecology and management, 2009)
This paper examines the past, present, and future use of the concept of historical range and variability (HRV) in land management. The history, central concepts, benefits, and limitations of HRV are presented along with a discussion on the value of HRV in a changing world with rapid climate warming, exotic species invasions, and increased land development. This paper is meant as a reference on the strengths and limitations of applying HRV in land management. Applications of the HRV concept have specific contexts, constraints, and conditions that are relevant to any application and are influential to the extent to which the concept is applied. These conditions notwithstanding, we suggest that the HRV concept offers an objective reference for many applications, and it still offers a comprehensive reference for the short-term and possible long-term management of our nation's landscapes until advances in technology and ecological research provide more suitable and viable approaches in theory and application.